2002
DOI: 10.1097/00007890-200210150-00018
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of posttransplant lymphoproliferative disease with prolonged rituximab treatment in intestinal transplant recipients

Abstract: Prolonged rituximab treatment, in association with reduction of immunosuppression and antiviral therapy, is highly efficient as part of the first-line treatment of CD20 B-cell PTLD after intestinal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…[7][8][9] Medical history of our patients was insignificant, except for coeliac disease in Patient 17. Patient 5 had history of acute lymphoblastic leukemia (ALL) and Patient 6 had history of renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 75%
“…[7][8][9] Medical history of our patients was insignificant, except for coeliac disease in Patient 17. Patient 5 had history of acute lymphoblastic leukemia (ALL) and Patient 6 had history of renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 75%
“…Although these antibodies are not currently available commercially, the introduction of rituximab, a humanized mouse anti-human CD20 antibody, has contributed markedly to care of patients with B-cell lymphomas. In PTLD, rituximab has shown effectiveness in several small case series (14,15). The largest group reported to date includes 32 patients, of whom 69% of patients responded (17).…”
Section: Discussionmentioning
confidence: 99%
“…This excess toxicity, particularly severe infections, is likely related to the already immunosuppressed state of patients. Recently, use of anti-B cell monoclonal antibodies has been explored, with encouraging results (13)(14)(15)(16)(17). Because of the rarity of PTLD, however, reports frequently include small patient numbers, making general observations difficult.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other reports suggest a response rate of 37% to 69% over an 8-to 32-month follow-up. 12,[19][20][21][22][23][24][25][26] The factors explaining the differences in rate response are still unknown; clear predictors of complete remission after rituximab also are not identified. In the largest prospective trial of rituximab in PTLD, Choquet and associates showed that in patients unresponsive to reduction of immunosuppression, adjunct rituximab resulted in a response rate of 44% (including 28% remission) at 3 months.…”
Section: Discussionmentioning
confidence: 99%